Ser71 Phosphorylation Inhibits Actin-Binding of Profilin-1 and Its Apoptosis-Sensitizing Activity - Wang, Faliang; Zhu, Cuige; Cai, Shirong; Boudreau, Aaron; Kim, Sun-Joong; Bissell, Mina; Shao, Jieya (Frontiers in Cell and Developmental Biology, 2021)
The essential actin-binding factor profilin-1 (Pfn1) is a non-classical tumor suppressor with the abilities to both inhibit cellular proliferation and augment chemotherapy-induced apoptosis. Besides actin, Pfn1 interacts with proteins harboring the poly-L-proline (PLP) motifs. Our recent work demonstrated that both nuclear localization and PLP-binding are required for tumor growth inhibition by Pfn1, and this is at least partially due to Pfn1 association with the PLP-containing ENL protein in the Super Elongation Complex (SEC) and the transcriptional inhibition of pro-cancer genes. In this paper, by identifying a phosphorylation event of Pfn1 at Ser71 capable of inhibiting its actin-binding and nuclear export, we provide in vitro and in vivo evidence that chemotherapy-induced apoptotic sensitization by Pfn1 requires its cytoplasmic localization and actin-binding. With regard to tumor growth inhibition by Pfn1, our data indicate a requirement for dynamic actin association and dissociation rendered by reversible Ser71 phosphorylation and dephosphorylation. Furthermore, genetic and pharmacological experiments showed that Ser71 of Pfn1 can be phosphorylated by protein kinase A (PKA). Taken together, our data provide novel mechanistic insights into the multifaceted anticancer activities of Pfn1 and how they are spatially-defined in the cell and differentially regulated by ligand-binding.